Identification of polyvalent protective immunogens from outer membrane proteins in Vibrio parahaemolyticus to protect fish against bacterial infection. (July 2016) - Peng, Bo; Ye, Jin-zhou; Han, Yi; Zeng, Li; Zhang, Jian-ying; Li, Hui
Abstract: Vaccination is one of the most effective and economic way to prevent infectious diseases in aquaculture. The development of effective vaccines, however, is still limited, especially for polyvalent vaccines, which are against multiple species. With this regard, identification of polyvalent protective immunogens, serving as polyvalent vaccines, became a key step in vaccine development. In the current study, 17 outer membrane proteins from Vibrio parahaemolyticus were identified as immunogens. Further, four of the 17 proteins including VP2309, VP0887, VPA0548 and VP1019 were characterized as efficiently protective immunogens against V. parahaemolyticus ' infection through passive and active immunizations in zebrafish. Importantly, these four proteins showed cross-protective capability against infections by Aeromonas hydrophila or/and Pseudomonas fluorescens, which shared similar epitopes with V. parahaemolyticus in homology of these proteins. Further investigation showed that the expression level of the four protective immunogens elevated in response to fish plasma in a dose-dependent manner. These results indicate that the four protective immunogens are polyvalent vaccine candidates in aquaculture. Highlights: Outer membrane proteins are a rich pool for polyvalent protective immunogens. Protective immunogens against Vibrios infection were characterized in zebrafish. Four polyvalent protective immunogens were identified from these immunogens. Similar epitopes were shared among these bacteria tested.